(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the pedagogical foundations of forming spiritual and moral values in primary school students and analyzes the effectiveness of applying modern teaching methods in the educational process. The role of moral education in the personal development of younger students is highlighted. The effectiveness of interactive methods, pedagogical technologies, and educational activities in developing honesty, patriotism, humanism, responsibility, and respect is substantiated. Based on practical experience, the impact of methodological approaches on educational quality is demonstrated.